Unusual presentation of acute pancreatitis mimicking strangulated inguinal hernia in a patient with bladder exstrophy: a rare case report - C., Vijayakumar; VJ, Reddy; T. P., Elamurugan; S., Jagdish (International Surgery Journal, 2017)
Acute pancreatitis (AP) is a common surgical emergency. Apart from the typical clinical presentation, unusual presentations are also reported in literature. Here we present a case of acute pancreatitis presenting as a strangulated inguinal hernia. A 45-year-old male with a neglected bladder exstrophy and reducible left inguinal hernia since childhood presented with pain over the left inguinal swelling for three days duration. Patient was initially managed conservatively since there were no signs of complication. After initial conservative management, the patient developed features of strangulation and was taken up for inguinoscrotal exploration. Intra-operatively, direct inguinal hernial sac was identified without any bowel obstruction. Further explorative laparotomy revealed an inflamed, bulky pancreas. The peri-pancreatic fluid aspirated intra-operatively had an amylase value of >4000 IU. Postoperative period was uneventful and patient was discharged after 8 days. In this case an already reducible hernia became irreducible due to pancreatic fluid collection and inflammation of contents. Lack of abdominal symptoms or signs can lead to misdiagnosis and unnecessary surgery. We report an unusual presentation of acute pancreatitis mimicking a strangulated inguinal hernia in a patient with bladder exstrophy.